Cybersecurity Challenges in IoT: A Comprehensive Assessment of Current Threats and Future Strategies - Acuña Acuña, Edwin Gerardo; Rosales Rojas, Ronald Ricardo (LACCEI, 2025)
The rapid expansion of Internet of Things (IoT) environments has brought transformative advancements alongside significant cybersecurity challenges. This study conducts a comprehensive assessment of IoT cybersecurity, analyzing current vulnerabilities and anticipating future threats. Key issues such as data privacy, integrity, and resilience against sophisticated attacks are explored, emphasizing the need for robust strategies to secure IoT ecosystems. The research highlights the layered IoT architecture and its unique security demands at the perception, network, and application levels. Furthermore, it examines the role of emerging technologies like 5G in mitigating these challenges and enabling more secure, scalable infrastructures. Through a detailed evaluation of existing countermeasures, vulnerabilities, and case studies—such as Tesla’s IoT-enabled systems—this work underscores the critical need for proactive approaches in cybersecurity. By integrating innovative methodologies and predictive strategies, this study aims to contribute to a more secure and resilient IoT landscape, fostering advancements in smart cities, healthcare, and industrial applications.